The rehabilitation of politics after 64 - Santos, Raimundo (FCL-UNESP Laboratório Editorial, 2007)
This article tries to explain how the PCB and other “publicists”, such as Fernando Henrique Cardoso , opposed and reacted to the conceptions based on the stagnant and catastrophic paradigm of the end of the 60’s and beginning of the 70’s: and how, when valuing the struggle in the legal field and the gradual changes , gave a priceless contribution to the birth of a democratic and political culture.